Correction: Fluorogenic bidirectional displacement probe-based real-time isothermal DNA amplification and specific visual detection of products. Issue 83 (3rd October 2016) - Ding, Xiong; Wang, Guoping; Sun, Jingjing; Zhang, Tao; Mu, Ying
Abstract : Correction for 'Fluorogenic bidirectional displacement probe-based real-time isothermal DNA amplification and specific visual detection of products' by Xiong Ding et al., Chem. Commun., 2016, 52, 11438–11441.